Macbeth Arabia: moral threat and cleansing-related construct accessibility in Arab women. Issue 2 (7th February 2018) - Thomas, Justin; Grey, Ian; Al-Romaithi, Salama
ABSTRACT: The "Macbeth effect" denotes a relationship between threatened moral integrity (e.g., guilt) and cleansing-related cognition and behaviours. This idea has received empirical support and may have implications for our understanding obsessive-compulsive disorder (OCD). Most previous explorations of the Macbeth effect, however, have been undertaken in Europe or North America. This study aimed to test the effect among Muslim, Arabic-speaking, citizens of the United Arab Emirates. Experimental participants ( N = 112) completed a task designed to threaten moral integrity (recalling past misdeeds), followed by a word-fragment completion task, where cleansing and non-cleansing completions were possible. A control-group ( N = 95) completed only the word-fragment completion task. Participants recalling past misdeeds made significantly more cleansing-related word-fragment completions than their control-group counterparts. This study extends evidence of a Macbeth effect to an Arabic-speaking Muslim population and may have implications for our understanding of OCD within this population.